Spatially targeting the distribution of agricultural input stockists in Malawi - Farrow, Andrew; Risinamhodzi, K; Zingore, Shamie; Delve, Robert J. (Elsevier, 2011)
Developing the rural agricultural input markets in sub-Saharan Africa can improve the current low productivity of smallholder farmers. Malawi has seen significant efforts in addressing the availability of agricultural inputs at village level in the last few years; for example, the improvement of rural agro-dealer networks. Nevertheless inputs are still difficult to obtain for many remote smallholder farmers. Spatial analysis can help in the expansion of input stockists, especially agro-dealer networks, by assessing the coverage of existing input outlets and deriving optimum locations for village-level input stockists. We address three research questions. First, what is the locational efficiency of the current village-level stockists of inputs (Citizens Network for Foreign Affairs Rural Agricultural Market Development Trust trained network of agro dealers and public sector)? Secondly, how many village-level stockists of markets are needed to reach 60% of the population in the central region of Malawi within one hour? Finally we address the potential spatial components of the sustainability of input stockists relating to the potential demand from smallholder farmers and the access to bulk supplies. The problem of finding the optimum location for village-level stockists of markets is addressed in two stages, using spatial analysis in conjunction with location allocation models. First, the locational efficiency of the existing network of stockists of inputs is determined, followed by the establishment of a set of optimal sites for village-level stockists of inputs. A final step explores the viability of stockists and calculates the population surrounding the stockists taking into account competition from other sources of inputs and the accessibility of the selected stockists to potential wholesalers who are bulk distributors of farm inputs. Our results show that locational efficiency can be assessed in terms of the differential access of households to resources and transport. Often, these differences are not considered in covering problems and can have a large effect on the physical access to inputs. The results can be used to define which areas are inherently difficult to serve with agricultural inputs and could inform efforts to provide incentives to remote areas. Further implications for input policies in Malawi are that improvements in road infrastructure might not directly benefit the poorest farmers (if they are walking) but could serve to reduce the wholesale prices and therefore the retail price. In addition, the improvement in roads might increase the number of potential customers of any particular stockist, with economies of scale allowing the reduction of prices while ensuring a satisfactory profit margin for the stockist. The results of our models imply that Citizens Network for Foreign Affairs may need to train stockists over a wider area to increase the access to inputs of those smallholder farmers with least resources.